IMPLEMENTASI IFRS TERHADAP KINERJA KEUANGAN (Study Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Anggi Pradipta Nugrohadi; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
. The purpose of this research is to examine the influence of implementation of International Financial Reporting (IFRS) on Financial Performance. This research test to compare before and after uses IFRS on Financial statement. This study purposes hypothesis that IFRS have positive influence financial ratio and firm sizeThe population of this research is manufacturing of listed firms in Indonesia Stock Exchange in year 2007 and 2012. Sampling method used is purposive sampling. Binary Logistic regression used to be analysis technique. The final amounts of sample are 61Result of this study show that IFRS have significant influenced on Operating profit margin, Market Value Book Value and Return of Shareholder Capital. IFRS have no significance on Leverage and Liquidity but have difference influence on firm size.